2016
DOI: 10.1590/1678-4685-gmb-2015-0148
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity in Brazilian barley using SSR markers

Abstract: Barley is a major cereal grown widely and used in several food products, beverage production and animal fodder. Genetic diversity is a key component in breeding programs. We have analyzed the genetic diversity of barley accessions using microsatellite markers. The accessions were composed of wild and domesticated barley representing genotypes from six countries and three breeding programs in Brazil. A total of 280 alleles were detected, 36 unique to Brazilian barley. The marker Bmag120 showed the greatest poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 45 publications
2
40
3
2
Order By: Relevance
“…The principal coordinate analysis has been widely used to represent genetic diversity in breeding programs in species such as maize (Van Inghelandt et al, 2010), sweet sorghum (Murray, Rooney, Hamblin, Mitchell, & Kresovich, 2009), rice (Choudhury et al, 2014;Roy et al, 2015), sweet potato (Su et al, 2017), and barley (Ferreira et al, 2016), among others. In all these works, associations among genotypes were revealed with the principal coordinate analysis.…”
Section: Comparison Of Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal coordinate analysis has been widely used to represent genetic diversity in breeding programs in species such as maize (Van Inghelandt et al, 2010), sweet sorghum (Murray, Rooney, Hamblin, Mitchell, & Kresovich, 2009), rice (Choudhury et al, 2014;Roy et al, 2015), sweet potato (Su et al, 2017), and barley (Ferreira et al, 2016), among others. In all these works, associations among genotypes were revealed with the principal coordinate analysis.…”
Section: Comparison Of Techniquesmentioning
confidence: 99%
“…Representation in plane, in a smaller number of dimensions, proves to be helpful for the identification of related genotypic groups (Cruz et al, 2011). Several studies used principal coordinates to demonstrate the divergence between genotypes using molecular data (Aitken et al, 2018;El-Esawi et al, 2018;Guzmán, Segura, Aradhya, & Potter, 2018;Taglioti et al, 2018;Wu et al, 2018;Ferreira et al, 2016;Zaher et al, 2011;Van Inghelandt, Melchinger, Lebreton, & Stich, 2010). Other studies were based on principal component analyses (Muller et al, 2018;Valcárcel, Peiró, Pérez-de-Castro, & Díez, 2018;Osawaru, Ogwu, & Dania-Ogbe, 2013;Santi et al, 2012;Jombart, Devillard, & Balloux, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were conducted in world to evaluate the genetic relationships among different barley genotypes using molecular markers (Hou et al, 2005;Ferreira et al, 2016). Pejic et al, (1998) reported that the information of polymorphism would be sufficient if more than 70 alleles were detected.…”
Section: Molecular Markers Based Genetic Variabilitymentioning
confidence: 99%
“…Simple sequence repeats (SSRs) considered a superior marker for assessment of genetic diversity, genetic relationship and phylogenetic development because this marker had high level of polymorphism, codominant inheritance, highly reproducibility, locus specificity and random distribution on the genome (Russell et al, 1997a). SSRs technique is powerful tool for genetic studies in barely breeding (Mohamed and Adel, 2012; Nandha and Singh, 2014 and Ferreira et al, 2016).…”
Section: Introductionmentioning
confidence: 99%